EDUKASI KESEHATAN PENCEGAHAN PENYAKIT DIARE PADA ANAK DI KELURAHAN INDARUNG PADANG - Syafwan, Metha Kemala Rahayu; Miswarti, Miswarti; Afnuhazi, Ridhyalla (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Diarrhea is still a major problem that causes death in toddlers. The role of mothers is very important in preventing diarrhea. Mothers' knowledge about diarrhea can affect how mothers handle diarrhea at home. The better the mother's knowledge, the better the mother's way of handling diarrhea, so that mothers can reduce the incidence of diarrhea in toddlers in the future. The purpose of this Community Service is to increase mothers' knowledge about preventing diarrhea in children in Indarung Village, Padang City. Health education uses lecture methods, questions and answers and hand washing practices. Knowledge evaluation by measuring pre-test and post-test knowledge after education. The results of the education showed an increase in mothers' knowledge about preventing diarrhea in children after being given education, knowledge in the sufficient category from 52.4% to 76.2%, and good knowledge increased to 38.1% from 14.3% before being given education. The conclusion is that there is an increase in mothers' knowledge about preventing diarrhea in children after being given health education. It is necessary to carry out continuous health education to the community in order to reduce cases of diarrhea in childrenKeywords: Children, Diarrhea, Education, Prevention